Produção contínua de ésteres metílicos de ácidos graxos a partir do destilado da desodorização do óleo de soja e acetato de metila em condições supercríticas - Vernier, Liara Jalime (2021)
This work aimed to investigate the continuous production of fatty acid methyl esters (FAME) from Soybean Oil Deodorization Distillate (SODD) and Methyl Acetate (MA) under supercritical conditions. SODD has been characterized and shown to be an acidic raw material with low water content and with a high content of free fatty acids. The experiments were carried out in a fixed bed reactor with 3 mm glass beads under 20 MPa, in which the influence of temperature (275°C; 300°C; 325°C), MA: SODD mass ratio (0.5:1; 1:1; 2:1) and residence time (7.5; 10; 20; 30; 40 min) in the production of FAME and triacetin (TA) was analyzed. The experimental condition that showed the best results was with a temperature of 300°C and a 1:1 methyl acetate to SODD mass ratio with 10 min of residence time, allowing to reach a FAME and TA yield of 84.6% and 11, 9% respectively. The 10-min residence time proved to be sufficient to achieve the highest FAME and TA yields in most of the conditions evaluated. The phenomenon of thermal decomposition of the esters at high temperature was verified and the mass transfer was evaluated with glass pearl diameters of 2; 3 and 4 mm. The highest thermal decomposition of fatty acid methyl esters (38.51%) was obtained at a temperature of 325°C in 40 minutes at an MA: SODD mass ratio of 0.5:1. The mass transfer with the smaller diameter pearl favored the triacetin yield. Thus, the use of low added value raw materials, such as SODD, proved to be efficient for the production of supercritical biodiesel with methyl acetate, allowing the occurrence of acid transesterification and interesterification